2021
DOI: 10.3389/fenrg.2021.690725
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Green Diesel Production by Hydrodeoxygenation of Palm Oil

Abstract: Transition to a new energy low carbon pool requires the gradual replacing of fossil fuels with other cleaner energies and biofuels. In this work, the environmental impact of renewable diesel production using an attributional life cycle assessment was evaluated by considering five stages: palm plantation-culture-harvest, palm oil extraction, palm oil refining, green (renewable) diesel production, and biofuel use. The functional unit was established as 1.6 × 10−2 m3 (13.13 kg) of renewable diesel. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In relation to that, over a period of 100 years, the current process showed a GWP of 9.87 kg CO 2 equiv/kg OP, including a direct contribution of 0.05 kg CO 2 equiv/kg OP. The process showed less contribution to global warming than conventional fuel as diesel has an approximate GWP of 79.93 kg CO 2 equiv . Concerning a full-fledged crude refining system, the GWP can be as high as 7,20,600 kg CO 2 equiv .…”
Section: Resultsmentioning
confidence: 99%
“…In relation to that, over a period of 100 years, the current process showed a GWP of 9.87 kg CO 2 equiv/kg OP, including a direct contribution of 0.05 kg CO 2 equiv/kg OP. The process showed less contribution to global warming than conventional fuel as diesel has an approximate GWP of 79.93 kg CO 2 equiv . Concerning a full-fledged crude refining system, the GWP can be as high as 7,20,600 kg CO 2 equiv .…”
Section: Resultsmentioning
confidence: 99%
“…Life Cycle Assessment (LCA) was employed to calculate GHG emission from POB production. LCA is a methodology commonly used to evaluate environmental impacts caused by industrial processes and services [13]. Calculation of GHG emissions from POB production uses a modified Biograce worksheet.…”
Section: Research Methods 21 Structure Of Intelligent System For Ghg ...mentioning
confidence: 99%
“…A life cycle assessment (LCA) is an internationally recognized tool for determining the associated environmental impacts with all the life cycle stages of biofuel production, processing and utilization, making biofuels more sustainable [ 8 ]. LCA is a methodology customarily employed to assess the impact of the product on the environment induced by industrial operations and services, from acquisition, manufacturing, and usage of raw material and its maintenance until the final disposal of products or utilization of services [ 115 ]. LCA can also suggest alternative sub-processes to make the process sustainable [ 35 ].…”
Section: Lifecycle Assessment and Sustainabilitymentioning
confidence: 99%
“…Further, gaining value-added by-products (glycerol, potassium sulfate, and other by-produce) has extra monetary and environmental benefits. Correspondingly, Arguelles-Arguelles et al [ 115 ] conducted an LCA study to produce renewable diesel from palm oil, and reported around a 110% decrease in CO 2 emissions compared to fossil diesel combustions. Nevertheless, this investigation also reported the impact of palm oil-based biodiesel on the environment and its toxicity to humans due to high agrochemical use in palm plantations.…”
Section: Lifecycle Assessment and Sustainabilitymentioning
confidence: 99%